The Socio-Demographic Portrait and Values of Russian Investment Apps Users - Ivan Iudin (Journal of Economic Sociology, 2024)
The past decade saw a rapid increase in the number of retail investors. The number of people holding brokerage accounts in Russia increased from 1 million in 2012 up to 23 million in 2022. This was mostly due to the lower market entry barriers and the widespread adoption of mobile investment apps. This paper examines the factors that influence the use of mobile investment apps, which have become the main tool for mass retail investors in the Russian stock market. This study employs data from the Monitoring Study of Society’s Digital Transformation conducted by ISSEK HSE in 2022. The sample was comprised of 9452 respondents aged 18 and above. The data suggests that despite a rapid increase in number of people with brokerage accounts, only about 4% of adult Russians engage in investment activities using mobile apps. Next, the associations between the use of investment apps and several groups of factors— socio-demographic characteristics, human capital, technological proficiency, and basic human values— were tested. It was demonstrated that investment apps users are typically young, affluent men with higher levels of human capital. They have higher education and engage in additional education and self-education activities. They also show strong innovativeness and low levels of technological discomfort. Their value orientations are characterized by autonomy, power, and universalism, while they do not value conformism and tradition.